Realizing Sustainable Communities through SDGs 12-Based Waste Management in Local Governments in Indonesia - Sapri, Sapri (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research aims to evaluate the implementation of the Sustainable Development Goals (SDGs) 12 in local government waste management practices in Indonesia. The study assesses the extent to which SDGs 12, responsible consumption and production, is incorporated into the waste management policies and systems in local governments in Indonesia. The findings reveal that although there have been some efforts to incorporate the principles of SDGs 12 into waste management policies, there is a lack of consistent implementation and enforcement in practice. This study highlights the need for local governments to prioritize the integration of SDGs 12 into their waste management practices to realize sustainable communities. The results of this study provide valuable insights for policymakers and stakeholders to improve the implementation of SDGs 12 in waste management in Indonesia.